2003
DOI: 10.1097/00041552-200301000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure, antihypertensive therapy and risk for renal injury in African-Americans

Abstract: Systolic blood pressure reduction in the range 130-139 mmHg is appropriate to reduce risk of nephropathy progression and cardiovascular risk in African-Americans with hypertensive nephrosclerosis. Moreover, a regimen that is initiated with an angiotensin-converting enzyme inhibitor should be the antihypertensive treatment of choice in African-Americans with kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
(29 reference statements)
0
7
0
1
Order By: Relevance
“…Family studies have shown that hypertension is more frequent in first-degree relatives of patients with primary glomerulopathies or diabetic nephropathy than in the general population (Adamczak et al 2002). Also, several studies have shown that African Americans are more likely than their white counterparts to develop hypertension-related ESRD (Marcantoni et al 2002;Hayden et al 2003;Kaperonis and Bakris 2003). Hypertension-related ESRD, or hypertensive nephropathy (HN), is a distinct histologic entity; however, in clinical practice, a kidney biopsy is not always performed when an affected individual presents with long-standing hypertension and renal failure.…”
mentioning
confidence: 99%
“…Family studies have shown that hypertension is more frequent in first-degree relatives of patients with primary glomerulopathies or diabetic nephropathy than in the general population (Adamczak et al 2002). Also, several studies have shown that African Americans are more likely than their white counterparts to develop hypertension-related ESRD (Marcantoni et al 2002;Hayden et al 2003;Kaperonis and Bakris 2003). Hypertension-related ESRD, or hypertensive nephropathy (HN), is a distinct histologic entity; however, in clinical practice, a kidney biopsy is not always performed when an affected individual presents with long-standing hypertension and renal failure.…”
mentioning
confidence: 99%
“…In the high-risk groups such as diabetics, DCCBs reduce new-onset dementia (85), which is a very critical parameter in improving the quality of life. DCCBs were effective in slowing progression of renal injury in African-Americans with hypertensive nephrosclerosis (38). Lercanidipine and losartan attenuated LDL oxidation in hypertensive diabetic patients (60).…”
Section: Therapeutic Advantage Of Angiotensin Receptor Blockers and Cmentioning
confidence: 99%
“…In addition, African Americans with target organ kidney damage are more likely than Whites to develop hypertension-end stage renal disease (ESRD), also called hypertensive nephropathy (HN; Kaperonis & Bakris, 2003). Strong, continuous associations of blood pressure level with risks of target organ damage to the brain, heart, and kidneys make high blood pressure a major risk factor for stroke, heart attack, and kidney failure.…”
Section: Comorbidities Associated With Genetic and Environmental Riskmentioning
confidence: 99%
“…The incidence of end-stage renal disease (ESRD) is 3.6 times higher in African Americans than in non-African Americans and hypertension induced nephrosclerois is more prevalent in African Americans compared to Whites thus attributing hypertension as the second leading cause of ESRD in African Americans (Kaperonis & Bakris, 2003). In addition, African Americans with essential hypertension have an increased susceptibility to glomerular hyperfi ltration in response to salt intake leading to progressive renal injury-damage due to a greater lifetime exposure to sustained blood pressure elevation (Arnett et al, 2001).…”
Section: Comorbidities Associated With Genetic and Environmental Riskmentioning
confidence: 99%